Gastric inhibitory polypeptide receptor antagonist, SKL‐14959, suppressed body weight gain on diet‐induced obesity mice. (25th March 2018) - Nakamura, T.; Tanimoto, H.; Mizuno, Y.; Okamoto, M.; Takeuchi, M.; Tsubamoto, Y.; Noda, H.
Summary: Objective: Gastric inhibitory polypeptide plays a role in glucose and lipid metabolism and is associated with obesity and insulin resistance. The objective of this study is to confirm the anti‐obesity effects of the gastric inhibitory polypeptide receptor antagonist, SKL‐14959, on diet‐induced obesity mice. Method: Diet‐induced obesity mice at 20 weeks of age were administered with or without SKL‐14959 for 96 d. Body weight and food intake were monitored throughout the experiment. Mice were sacrificed, and physiological and biochemical markers were measured, and then histochemical and gene expression analyses were also performed. In further studies, mice were orally gavaged with [ 14 C]‐oleic acid to investigate the excursion of digested lipids. Results: SKL‐14959 significantly suppressed weight gain without affecting food intake, decreased triacylglycerol contents in the liver and the muscle and the intensity stained with oil‐red in the liver. It also improved plasma glutamic pyruvic transaminase and 3‐hydroxybutyrate levels in addition to notably down‐regulated relative gene expression of srebf1 and dgat1 in the liver despite not altering in the adipose tissue . Furthermore, SKL‐14959 showed remarkable inhibition of lipid uptake in the adipose tissue after the oil challenge. Conclusion: SKL‐14959 inhibited lipids uptake and improved lipids metabolism, results in suppression of body‐weight gain.